2010
DOI: 10.1007/s10661-010-1822-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pollutants on fish collected from different parts of Shatt Al-Arab River: a histopathological study

Abstract: In this study, a total of 120 fish specimens of common carp (Cyprinus carpio), were caught at four different stations in Shatt Al-Arab (Hareer, Garmat Ali, Al-Maqal and Abual-Khasib). The histological changes in the gills of fish were detected microscopically. Results show that the Shatt Al-Arab is polluted by some different sources of pollutants including power stations, paper industry, oil refineries, petrochemical industry, chemical fertilizer companies and the sewage system and overfishing and the applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 31 publications
(30 reference statements)
0
17
0
Order By: Relevance
“…Furthermore, these kinds of tissue alterations were already reported for a wide variety of aquatic xenobiotics (Cengiz and Unlü 2003;Camargo and Martinez 2007;Á lvarez-Muñoz et al 2009). Gills alterations usually lead to hypoxia, respiratory failure and ionic and acid-base imbalances (Hawkins et al 1984;Alazemi et al 1996;Yasser and Naser 2011). Gill pathological indexes were not significantly altered in individuals exposed to zinc pyrithione, suggesting that tissue alterations are minimal, and fish health was not significantly compromised.…”
Section: Figmentioning
confidence: 99%
“…Furthermore, these kinds of tissue alterations were already reported for a wide variety of aquatic xenobiotics (Cengiz and Unlü 2003;Camargo and Martinez 2007;Á lvarez-Muñoz et al 2009). Gills alterations usually lead to hypoxia, respiratory failure and ionic and acid-base imbalances (Hawkins et al 1984;Alazemi et al 1996;Yasser and Naser 2011). Gill pathological indexes were not significantly altered in individuals exposed to zinc pyrithione, suggesting that tissue alterations are minimal, and fish health was not significantly compromised.…”
Section: Figmentioning
confidence: 99%
“…Kock and Hofer [32] reported that even low concentration of heavy metals in the water may results in high concentration of them in fish flesh the point which is of great concern regarding to fish health directly and human health indirectly [33]. Prolonged exposure of fish to heavy metals causes several histopathological changes especially in the fish gills [34][35][36] and since gills are the respiratory and osmo-regulatory organ of fish, these histopathological changes might impair the gill respiratory function by reducing respiratory surface area resulted in hypoxia, respiratory failure problems [37][38][39] which may lead to fish death [40].…”
Section: Discussionmentioning
confidence: 99%
“…Kock and Hofer [33,34] reported that even low concentration of heavy metals in the water may results in high concentration of them in fish flesh the point which is of great concern regarding to fish health directly and human health indirectly. Prolonged exposure of fish to heavy metals causes several histopathological changes especially in the fish gills [35][36][37] and since gills are the respiratory and osmo-regulatory organ of fish, these histopathological changes might impair the gill respiratory function by reducing respiratory surface area resulted in hypoxia, respiratory failure problems [38][39][40] which may lead to fish death [41]. Parasitic species can be found on every living organisms, their presence in their hosts is generally at equilibrium in aquatic ecosystem [42].…”
Section: Discussionmentioning
confidence: 99%